2020
DOI: 10.5195/jwsr.2020.998
|View full text |Cite
|
Sign up to set email alerts
|

Power and Politics in the World-System

Abstract: While various researchers and practitioners agree that it will be hard to restructure our current global and local systems to adapt to and mitigate climate change, there is unsurprisingly great disagreement in how and if this can be accomplished and on what level(s), or if this is even what needs to be accomplished. These conversations have continued with the introduction of the “Anthropocene.” The dominant interpretation of the concept poses several solutions, one being national government restructuring to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Thus, the central contribution of this analysis is addressing major methodological differences across the social sciences, where I incorporate measures of FDI used in sociological studies of FDI and analyze three unique samples of countries that have attracted much social scientific attention. The analysis results appear to suggest that inward FDI stocks as a percentage of GDP are inversely associated with CO 2 emissions per capita in all three samples of countries, which slightly differs from the findings of previous cross-national studies that investigate the FDI and CO 2 emissions per capita relationship (Hargrove et al 2021;Jorgenson et al 2007;Shandra et al 2004;Sommer and Hargrove 2020). There are also scholarly conversations regarding domestic investment, especially in investigations of the environmental impacts of foreign investment as a major point of contention is that the source of investment does matter (e.g., Grimes and Kentor 2003;Jorgenson et al 2007;Kentor and Grimes 2006;Long et al 2017;McKinney 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, the central contribution of this analysis is addressing major methodological differences across the social sciences, where I incorporate measures of FDI used in sociological studies of FDI and analyze three unique samples of countries that have attracted much social scientific attention. The analysis results appear to suggest that inward FDI stocks as a percentage of GDP are inversely associated with CO 2 emissions per capita in all three samples of countries, which slightly differs from the findings of previous cross-national studies that investigate the FDI and CO 2 emissions per capita relationship (Hargrove et al 2021;Jorgenson et al 2007;Shandra et al 2004;Sommer and Hargrove 2020). There are also scholarly conversations regarding domestic investment, especially in investigations of the environmental impacts of foreign investment as a major point of contention is that the source of investment does matter (e.g., Grimes and Kentor 2003;Jorgenson et al 2007;Kentor and Grimes 2006;Long et al 2017;McKinney 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…2007; Shandra et al. 2004; Sommer and Hargrove 2020). There are also scholarly conversations regarding domestic investment, especially in investigations of the environmental impacts of foreign investment as a major point of contention is that the source of investment does matter (e.g., Grimes and Kentor 2003; Jorgenson et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their research showed that rises in fuel prices, which may be viewed as a stand-in for fuel taxes, have a significant impact on the volume of maritime transport, the use of bunker fuel, and carbon emissions from the global shipping industry. Using environmental taxes as a percentage of overall tax revenue, Sommer and Hargrove ( 2020 ) looked at the connection between environmental governance and CO2 emissions for 75 different countries. According to their analysis, reduced CO2 emissions are related to better environmental governance, which is reflected in higher environmental levies.…”
Section: Literature Reviewmentioning
confidence: 99%